Expression Analysis of miRNAs Targeting PIK3CA and AKT1 Genes of PI3K Signaling Pathway in Breast Cancer Cells. - Razaviyan, Javad; Hadavi, Razie; Mohammadi-Yeganeh, Samira (Galen Medical Journal, 2023)
Background: MicroRNAs (miRNAs) are key gene regulators that are involved in many biÂological and also pathological processes, including breast cancer. Breast cancer is the most common form of malignancies in women and requires new therapies and biomarkers. Different signaling pathways, such as Phosphoinositide 3-kinase (PI3K) signaling pathway are involved in breast cancer and can be new candidates for targeted therapies based on miRNAs. The aim of this study was to predict miRNAs targeting Phosphatidylinositol-4, 5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) and serine/threonine kinase 1 (AKT1) genes of PI3K cascade bioinformatically and to analyze their expression in breast cancer. Materials and Methods: Bioinformatic software and tools were used to predict miRNAs targeting PIK3CA and AKT1 genes. MCF-7 and MCF-10A cell lines were cultured as breast cancer and control cells respecÂtively. RNA extraction, cDNA synthesis, and quantitative real-time PCR were performed. REST 2009Â® was utilized to analyze the expression of miRNAs and their target genes. Results: The results of our bioinformatic predictions indicated that miR-576-5p, miR-501-3p, and miR-3143 can be the first candidate miRNAs targeting PI3K signaling pathway. Data analyses demonÂstrated that PIK3CA and AKT1 genes were up-regulated while all bioinformatically predicted miRNAs were down-regulated in MCF-7 cell line compared to the normal cells. Conclusion: The results of our study demonstrated that PIK3CA and AKT1 can be targeted by miR-576-5p and miR-501-3p respectively. Furthermore, miR-3143 can target both mRNAs. Since these miRNAs target oncogenes, they can be proposed for new complementary targeted therapies in breast cancer patients. [GMJ.2017;6(4):338-45] DOI: 10.22086/gmj.v6i4.925